Screening for hearing loss in the setting of primary care, and the most common used tests - Turkistani, Ohoud Adel; Arqan, Wjdan Abduljlil Al; Alkhaibry, Rania Saad; Ayoub, Yazan Adnan; Alhuthali, Rawan Mesfer; Alsayegh, Hussain Ali; Momenah, Kholoud Khaled; Mansour, Mohammed Hamad Al; Felemban, Mohannad Sami; Alqahtani, Ahmed Ali; Ameen, Jasem Mohammad (International Journal Of Community Medicine And Public Health, 2021)
Hearing loss is considered among the most common chronic disorders affecting people worldwide, especially older adults and geriatrics. More than half of older adults have age-related hearing loss, which worsens with age. The role of public health to estimate and manage the issue is crucial as early screening and management for hearing loss patients can be promising. The symptoms and signs of hearing loss can appear one up to two years before the significant hearing affection. Major lessons learned from this review are that elderly individuals and geriatrics are the most common targeted population for age-related hearing loss, followed by ear wax accumulation. Therefore, routine checkup for people who are 50 years for audiological disorders is a must. Associated disorders secondary to hearing loss include depression and anxiety, which significantly burden productivity over time. To our knowledge, we performed the first complex review regarding the screening for hearing loss within the setting of primary care centers and mentioned the most standard test used to diagnose and detect the issue as early as possible.